Nano-structured and functionalized surfaces for cytocompatibility improvement and bactericidal action - Slepicka, Petr; Kasalkova, Nikola Slepickova; Siegel, Jakub; Kolska, Zdenka; Bacakova, Lucie; Svorcik, Vaclav (Biotechnology advances, 2015)
The field of material surface modification with the aim of biomaterial construction involves several approaches of treatments that allow the preparation of materials, which positively influence adhesion of cells and their proliferation and thus aid and improve tissue formation. Modified materials have a surface composition and morphology intended to interact with biological systems and cellular functions. Not only surface chemistry has an effect on material biological response, surface structures of different morphology can be constructed to guide a desirable biological outcome. Nano-patterned material surfaces have been tested with the aim of how surface geometry and physical properties on a micro- and nano-scale can affect cellular response and influence cell adhesion and proliferation. Biological functionality of solid state substrates was significantly improved by the irradiation of material with plasma discharge or laser treatment. Commonly used "artificial" polymers (e.g. polyethylene (PE), polystyrene (PS), polytetrafluoroethylene (PTFE), polyethylene terephthalate (PET), polyethylene naphthalate (PEN)) and biopolymers (e.g. Poly-l-Lactic acid (PLLA), polymethylpentene (PMP)) were treated with aim of biocompatibility improvement. The treatment of polymer/biopolymer substrates leads to formation of ripple or wrinkle-like structures, supported also with heat treatment or other subsequent surface processing. Several types of chemically different substances (e.g. metal or carbon nano-particles, proteins) were grafted onto material surfaces or built into material structures by different processes. Surface physico-chemical properties (e.g. chemistry, charge, morphology, wettability, electrical conductivity, optical and mechanical properties) of treated surfaces were determined. The enhancement of adhesion and proliferation of cells on modified substrates was investigated in vitro. Bactericidal action of noble metal nano-particles (e.g. Au, Ag) on polymers was characterized. The influence of metal nano-particle grafting by using metal nano-particle suspension prepared by "green" methods was determined. Micro- and nano-patterned surfaces can be constructed as tissue scaffolds with specific functions regarding cell adhesion and proliferation or potential biosensor applications.
Keywords: lasery; povrchové vlastnosti; Bactericidal action of noble metal nano-particles; Nanostructures; testování materiálů; Lasers; Laser; Materials Testing; antibakteriální látky; nanostruktury; Surface properties; Polymers; Surface modification; polymery; Anti-Bacterial Agents; Tissue engineering; Cell–material interaction; Surface Properties; Plasma; Nano-particle grafting